Explosive strength, velocity and specific motor skills in soccer junior players: A correlational study - M.C. Marques; B. Travassos; R. Almeida (Desafio Singular, 2010)
The main aims of the present study were: a) to evaluate speed and technical skills, and b) to examine the relationship between those measures. Thirty-seven junior soccer players under 19 years of age from three amateur soccer teams were evaluated using vertical and horizontal jump tests, 30m sprint speed test, change of direction test, dribble test and the kicking speed test. The significant correlations found help to understand this population's performance.